ANALYSIS OF THE MODERN CLEANING OF GONDOLA CARS FROM THE REMNANTS OF BULK CARGOES - Романович, Євгеній Валентинович; Повороженко, Євген Віталійович (Eastern-European Journal of Enterprise Technologies, 2010)
Constructions of the most widespread vibration machines for mechanization of cleaning of semi-wagon from tailings of friable loads are considered. The analysis of their dignities and failing is executed. On the basis of the conducted analysis the construction of a new vibration cleansing machine is offered.